2016
DOI: 10.1016/j.bbrc.2016.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Berberine suppressed epithelial mesenchymal transition through cross-talk regulation of PI3K/AKT and RARα/RARβ in melanoma cells

Abstract: Berberine is a natural compound extracted from Coptidis rhizoma, and accumulating proof has shown its potent anti-tumor properties with diverse action on melanoma cells, including inhibiting cancer viability, blocking cell cycle and migration. However, the mechanisms of berberine have not been fully clarified. In this study, we identified that berberine reduced the migration and invasion capacities of B16 cells, and notably altered pluripotency of epithelial to mesenchymal transition associated factors. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 28 publications
5
42
1
Order By: Relevance
“…The low expression of PTEN results in its disability to effectively inhibit the abnormal activation of the PDK/Akt pathway, and thus leads to tumor migration, which is associated with the highest occurrence rate in prostate, endometrial cancer, glioma and MM (10). As is reported, PTEN gene changes can be seen in 30–50% of MM cell lines and 5–20% of MM cells (9,11). The activated PI3K/Akt may further activate its downstream molecule mTOR through the TSC1/2 complex, and the activated mTOR can activate its two downstream molecules subsequently, which are the translation inhibitory molecule eIF-4E binding protein 1 (4E-BP1) and ribosomal protein p70S6K (10,12).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The low expression of PTEN results in its disability to effectively inhibit the abnormal activation of the PDK/Akt pathway, and thus leads to tumor migration, which is associated with the highest occurrence rate in prostate, endometrial cancer, glioma and MM (10). As is reported, PTEN gene changes can be seen in 30–50% of MM cell lines and 5–20% of MM cells (9,11). The activated PI3K/Akt may further activate its downstream molecule mTOR through the TSC1/2 complex, and the activated mTOR can activate its two downstream molecules subsequently, which are the translation inhibitory molecule eIF-4E binding protein 1 (4E-BP1) and ribosomal protein p70S6K (10,12).…”
Section: Introductionsupporting
confidence: 65%
“…PTEN can dephosphorylate phosphatidylinositol 3,4,5-trisphosphate (PIP3), and thus, weaken the PI3K-derived activation signal and indirectly inhibit the activation of Akt (9). The low expression of PTEN results in its disability to effectively inhibit the abnormal activation of the PDK/Akt pathway, and thus leads to tumor migration, which is associated with the highest occurrence rate in prostate, endometrial cancer, glioma and MM (10).…”
Section: Introductionmentioning
confidence: 99%
“…Today, N‐cadherin is regarded as a vital marker of EMT . Neoexpression or upregulated expression of N‐cadherin has been reported to accelerate migration and invasion of cancer cells, which showed a contrary function to those of E‐cadherin . This process of reciprocally downregulating E‐cadherin and upregulating N‐cadherin is known as cadherin switching that characterizes EMT .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that N‐cadherin boosts the combination of fibroblast growth factor (FGF) with the receptor to initiate FGFR signal transduction, thereby inducing signalling cascades that promote migration and invasion of cancer cells . Furthermore, studies have shown that N‐cadherin promotes cells survival and protects cancer cells from apoptosis by activating the phosphatidylinositol 3‐kinase (PI3K)‐AKT (also known as protein kinase B) pathway . Therefore, N‐cadherin presents distinct functions from its adhesion activity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, RARbeta and RARgamma signaling were upregulated. BBR treatment may reverse EMT in melanoma cells [279]. …”
Section: Introductionmentioning
confidence: 99%